Water-holding capacity, colour stability and sensory characteristics in meat (M. longissimus dorsi) from reindeer fed two different commercial feeds - Wiklund, Eva; Johansson, Lisbeth (Rangifer, 2011)
Twenty reindeer calves (age 10 months) were included in the study. They were all fed one of two different pelleted feed mixtures ad libitum for two months before slaughter. Ten calves were fed a control diet of conventional pellets (CPD) (Renfor Bas, Lantmännen, Holmsund, Sweden) and ten calves received pellets enriched with linseed cake (LPD). The reindeer were slaughtered according to standard procedure at Arvidsjaur Renslakt AB, a reindeer slaughter plant in Arvidsjaur, Sweden. At 1 day post mortem, both longissimus dorsi (LD) muscles from each carcass were excised. The left LD was used for sensory evaluation and the right LD for colour and water-holding capacity measurements. The right LD was cut in 4 pieces that were randomly allocated to storage times of 1 day, 1, 2, or 3 weeks at + 4 °C. Samples allocated for storage were vacuum packaged. Evaluation of meat colour was carried out after each of the four storage times while drip loss/purge was registered after 1, 2, and 3 weeks storage at + 4 °C. The left LD muscles were vacuum packaged, frozen at -20 °C and kept frozen until preparation for sensory evaluation. No significant differences were found in carcass quality (carcass weight, EUROP carcass conformation and fat scores), meat colour stability and water-holding capacity of LD samples when comparing the two treatment groups LPD and CPD. However, sensory panellists judged samples from LPD fed reindeer to have a tendency (not significant) to be more tender (P= 0.06) and juicy (P=0.07) than the meat samples from CPD fed reindeer. No flavour differences were found when comparing meat samples from the two treatment groups.